Monocrystalline silicon solar cell efficiency dependence on potassium silicate additive in texturing process with a study on the effect of the active material - Salwa Abdel Naser; Ahmed A. Zaki Diab; Saleh Al Dawsari; Mohamed A. Ismeil; Mohamed Zahran (PLoS ONE, 2026)
Texturing is a critical process for enhancing monocrystalline silicon solar cell efficiency by reducing surface reflectance and improving light absorption. This study investigates the effect of introducing potassium silicate (K₂SiO₃) as an additive during alkaline texturing while simultaneously reducing the concentration of isopropyl alcohol (IPA)—a volatile organic solvent commonly employed to control anisotropic etching, ensuring uniform pyramid formation. The analysis examines surface morphology, particularly the pyramid structures formed on silicon wafers, and evaluates changes in photovoltaic performance with and without K₂SiO₃ addition. Wafers were weighed before and after texturing to quantify material removal. Weight loss measurements showed that texturing with 500 mL IPA alone (without K₂SiO₃) resulted in excessive etching (1.057 g, exceeding the optimal range of 0.6–1.0 g), while addition of 5 g K₂SiO₃ with reduced IPA (250 mL) yielded controlled weight loss (0.942 g) within the acceptable range. This demonstrates that potassium silicate regulates the etching process, preventing over-texturing and improving surface quality. Following plasma-enhanced chemical vapor deposition (PECVD), the thickness and refractive index of the deposited SiNₓ anti-reflection coating were measured using ellipsometry, yielding values of 87.1 nm and 1.99 for wafers textured without K₂SiO₃ (500 mL IPA), and 81.6 nm and 1.93 for those processed with K₂SiO₃ (250 mL IPA + 5 g K₂SiO₃). Completed solar cells were characterized using current–voltage (I–V) measurements to determine electrical parameters and efficiency. All experiments were conducted at the Egyptian-Chinese Laboratory for Renewable Energy Applications. Pyramid homogeneity was further analyzed using scanning electron microscopy (SEM). Statistical analysis including ANOVA and Tukey HSD post-hoc testing was performed to validate the significance of observed efficiency improvements.